Fire on the water : sailors, slaves, and insurrection in early American literature, 1789-1886 - Warren, Lenora (Transits (Bucknell University), 2019)
"Lenora Warren tells a new story about the troubled history of abolition and slave violence by examining representations of shipboard mutiny and insurrection in late eighteenth- and early nineteenth-century Anglo-American and American literature. Fire on the Water centers on five black sailors, whose experiences of slavery and insurrection either inspired or found resonance within fiction: Olaudah Equiano, Denmark Vesey, Joseph Cinque, Madison Washington, and Washington Goode. These stories of sailors, both real and fictional, reveal how the history of mutiny and insurrection is both shaped by, and resistant to, the prevailing abolitionist rhetoric surrounding the efficacy of armed rebellion as a response to slavery. Pairing well-known texts with lesser-known figures (Billy Budd and Washington Goode) and well-known figures with lesser-known texts (Denmark Vesey and the work of John Howison), this book reveals the richness of literary engagement with the politics of slave violence"--